2013
DOI: 10.1002/jgrb.50130
|View full text |Cite
|
Sign up to set email alerts
|

Radiography of a normal fault system by 64,000 high‐precision earthquake locations: The 2009 L'Aquila (central Italy) case study

Abstract: .[1] We studied the anatomy of the fault system where the 2009 L'Aquila earthquake (M W 6.1) nucleated by means of~64 k high-precision earthquake locations spanning 1 year. Data were analyzed by combining an automatic picking procedure for P and S waves, together with cross-correlation and double-difference location methods reaching a completeness magnitude for the catalogue equal to 0.7 including 425 clusters of similar earthquakes. The fault system is composed by two major faults: the high-angle L'Aquila fau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
239
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(256 citation statements)
references
References 87 publications
(139 reference statements)
15
239
1
1
Order By: Relevance
“…The rough estimate of the width of this zone corresponds to a smaller wavelength in the considered frequency band of 0.1-1 Hz and is about 1.5 km. This is in a good agreement with the recent results of Valoroso et al (2013), who estimated the width of the seismically active L'Aquila fault zone using analysis of high-precision earthquake locations spanning 1 year. They showed that the width of the fault zone varies along strike from 0.3 km, where the fault exhibits the simplest geometry and experienced peaks in the slip distribution, up to 1.5 km at the fault tips, with an increase in the geometrical complexity.…”
Section: Discussionsupporting
confidence: 92%
“…The rough estimate of the width of this zone corresponds to a smaller wavelength in the considered frequency band of 0.1-1 Hz and is about 1.5 km. This is in a good agreement with the recent results of Valoroso et al (2013), who estimated the width of the seismically active L'Aquila fault zone using analysis of high-precision earthquake locations spanning 1 year. They showed that the width of the fault zone varies along strike from 0.3 km, where the fault exhibits the simplest geometry and experienced peaks in the slip distribution, up to 1.5 km at the fault tips, with an increase in the geometrical complexity.…”
Section: Discussionsupporting
confidence: 92%
“…4c), although in nearby areas the observed Vp and Vs values correspond to the characteristic velocities of the Meso-Cenozoic limestones and terrigenous rocks Di Stefano et al, 2011). The sequence is well described by a detailed doubledifference catalog of relocated events (3000 events with M ≥ 1.9 from Chiaraluce et al, 2011; ∼ 64 000 events of all magnitudes from Valoroso et al, 2013). When coupled with moment tensor solutions for the largest shocks (M w ≥2.7; Herrmann et al, 2011), these data allow imaging of individual faults activated during this complex sequence in great detail (Fig.…”
Section: The 6 April 2009 Earthquakementioning
confidence: 78%
“…It includes both velocimetric and accelerometric signals recorded by temporary and permanent stations of the National Seismic Network (RSN, Rete Sismica Nazionale) operated by INGV and by the national Accelerometric Network (RAN, Rete Nazionale Accelerometrica) operated by the Italian Civil Protection Department (DPC). For each event, the local magnitude is computed accordingly to Di Bona (2016) and the P-and S-wave onsets obtained by an automatic phase-picker (Spallarossa et al 2016) are used to relocate the hypocentres using the regional 1-D velocity model reported in Valoroso et al (2013). A final visual inspection is applied to verify the automatic arrival times and to discard clipped or distorted signals.…”
Section: Data Setmentioning
confidence: 99%